SOSIALISASI PEMBUATAN DAN PENGENALAN NOMOR INDUK BERUSAHA (NIB) UMKM MELALUI SISTEM ONLINE SINGLE SUBMISSION (OSS) DI PEKON SUKOHARJO 1 - Adi Prasetia Nanda; Elisabet Yunaeti Anggareni; Muhammad Islamadi; Ahmad Syarifuddin (LP3K Lampung, 2022)
The existence of increasingly sophisticated technology, it encourages the government to create government programs that are advanced and can adapt to current developments. One of them is in the field of licensing, which is realized with the existence of Online Single Submission (OSS) by the Investment and One-Stop Service Office, Pringsewu Regency, Sukoharjo 1, is a village in Sukoharjo District, Pringsewu Regency, Lampung has approximately one hundred MSMEs registered with the Cooperatives and MSMEs Office. Pringsewu Regency. Realizing the importance of providing awareness and understanding to Micro, Small, and Medium Enterprises (MSMEs) actors of the importance of having a business license, the STMIK Pringsewu service team conducted training to help residents, especially MSME actors, be given knowledge and understanding of business licensing. There are several methods used in carrying out this service, namely: MSME data collection, surveys, and outreach, making MSME NIB, and submission of NIB documents. The results of this PKM activity are that business actors can know the importance of business legality and business registration with the OSS institution so that MSMEs in Pekon Sukoharjo 1 get business protection and ease of access to capital, and empowerment from the government and assistance in developing micro, small and medium enterprises.